2018
DOI: 10.1016/j.ymthe.2018.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Local Immunomodulation with Anti-inflammatory Cytokine-Encoding Lentivirus Enhances Functional Recovery after Spinal Cord Injury

Abstract: Trauma to the spinal cord and associated secondary inflammation can lead to permanent loss of sensory and motor function below the injury level, with the resulting environment serving as a barrier that limits regeneration. In this study, we investigate the localized expression of anti-inflammatory cytokines IL-10 and IL-4 via lentiviral transduction in multichannel bridges. Porous multichannel bridges provide physical guidance for axonal outgrowth with the cytokines hypothesized to modulate the neuroinflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
95
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(101 citation statements)
references
References 70 publications
4
95
2
Order By: Relevance
“…A number of groups have reported that IL10 treatment after a thoracic SCI can lead to intraspinal sparing of neurons, axons, and lesion size that is associated with improved locomotor function [23][24][25][26][27][28][29]. We have also previously demonstrated in a left-sided, thoracic SCI that IL10 can shift the inflammatory milieu toward a pro-regenerative phenotype, which was associated with significantly improved locomotor function [37,38] and consistent with the results here in the cervical model. Thoracic injuries that employ behavioral tests such as the basso mouse scale for locomotion, which is controlled by central pattern generators (CPGs) that can be unilaterally activated to initiate bilateral locomotor behavior, may not fully capture the deficit from the unilateral injury.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A number of groups have reported that IL10 treatment after a thoracic SCI can lead to intraspinal sparing of neurons, axons, and lesion size that is associated with improved locomotor function [23][24][25][26][27][28][29]. We have also previously demonstrated in a left-sided, thoracic SCI that IL10 can shift the inflammatory milieu toward a pro-regenerative phenotype, which was associated with significantly improved locomotor function [37,38] and consistent with the results here in the cervical model. Thoracic injuries that employ behavioral tests such as the basso mouse scale for locomotion, which is controlled by central pattern generators (CPGs) that can be unilaterally activated to initiate bilateral locomotor behavior, may not fully capture the deficit from the unilateral injury.…”
Section: Discussionsupporting
confidence: 89%
“…After 48hrs, the supernatant was collected and the virus was precipitated using PEG-It (Systems Biosciences, Palo Alto, CA, #LV825A-1) and stored at -80°C until use. Prior to surgery, 4e7 IFU of virus was loaded onto each PLG scaffold, which were fabricated as previously described using the gas foaming technique to fuse PLG particles into a matrix [20,38,40]. Using the particulate leaching technique, 63-106 µm NaCl served as sacrificial templates for pores to allow cell infiltration into the scaffold and a sugar mixture pulled into nine 150-250 µm diameter A-P parallel strands served as sacrificial templates for conduits to guide nerve growth [36,41].…”
Section: Lentiviral Gene Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…M2 macrophage activation facilitates spinal cord repair in SCI, which is associated with the promotion of neuronal survival 37 . Integrating the previous findings, the current observations that Rictor overexpression reduced apoptosis in host neurons and oligodendrocytes in the injured lesion may benefit the neurite outgrowth and synaptic plasticity after traumatic SCI 38 …”
Section: Discussionsupporting
confidence: 67%
“…2A peptides can lead to high levels of downstream protein expression compared to other strategies for multi gene co-expression and are small enough to not negatively interfere with the function of the coexpressed genes 21 . IL-10 can alter the phenotype of invading macrophages towards a pro-regenerative phenotype and lead to improved spinal cord regeneration 22,23 , while NT-3 expression can promote neuron survival and axonal elongation 19 . Herein, we investigated the potential for co-expression to influence macrophage phenotypes, axonal elongation and myelination, and source of the myelination at 12 weeks post injury, with subsequent studies assessing the functional benefits of co-delivery.…”
Section: Introductionmentioning
confidence: 99%